An Application of Portfolio Insurance Strategies in FOREX market - Ma, Jun (2010)
This dissertation proposes two dynamic capital allocation methods of hedging foreign exchange risks of payables denominated in foreign currencies. One strategy is synthetic call option strategy based on currency pricing formula; the other strategy is constant proportion portfolio insurance (CPPI) strategy based on linear rule. Monte Carlo simulation is used to test the performance of the strategies. For synthetic call option strategy, the effect of changing initial wealth on saving performance and hedging performance is revealed. I find that increasing initial wealth can improve both saving performance and hedging performance of synthetic call option strategy. For CPPI strategy, extensive combinations of initial wealth cases and multiples are tested. I find that different multiples change the distribution pattern of CPPI strategy dramatically. In general, bigger multiples will reduce the hedging performance but as long as the multiple is smaller than 21, the floor level can always be protected. Because of effect of changing multiples on saving performance of CPPI is complicated, I propose saving premium at risk and minimum saving ratio to seek the optimal multiple for each initial wealth case. The performance comparisons between synthetic call option strategy and CPPI strategy show that CPPI strategy dominates the competitor in terms of hedging performance while synthetic call option strategy has better saving performance on average. I find that the CPPI strategy is more attractive to hedgers if foreign currency is expected to appreciate while the synthetic call option strategy is more attractive if foreign currency is expected to depreciate. I propose a method to improve the hedging performance of synthetic call option strategy and find that it cannot be used if initial wealth is not sufficient enough.